Philosophy of education is still fascinating educationists: A biblio-appraisal from 1929 - 2019 - Baladi, Zameer Hussain; Qarni, Saleh Ali Al; Yasmin, Tahira; Ali, Taimoor (International Journal of Humanities and Education Development (IJHED), 2020)
Purpose: This study design to explore the literature produced and published in journals indexed in the Scopus-Elsevier database in terms of educational philosophy. Methods: The data acquired from the journals indexed in the Scopus-Elsevier database for analysis. This study divided into eight spells and covered 92 years to examine; year-wise, type of documents, primary classification of subjects, authors' contribution, an affiliation of the first author with country, and the statistical position of the journal from 1929 - 2019. Results: Total 1587 different types of documents written by 2168; 1.3% of authors with an average of 17.2 per annum. The data distributed in 10 categories published from 1929 – 2019. Research articles 1070; 67.4%, book chapters 164; 10.3%, and review articles 95; 6% standing on top slots. Spell 2011 – 2019, published maximum research in every category. The majority of 1189; 75% articles written by the single or solo author, followed by 242; 15% two authors, the authors of 28; 1.7% not traced. A total of 697 places published 1587 documents. Journal of Educational Theory 113; 7.1%, Journal of Educational Philosophy and Theory 103; 6.4%, Journal of Philosophy of Education 92; 5.8%, and Journal of Studies in Philosophy and Education 75; 4.7% provides maximum spaces in publications as on single entity. Social Sciences covered 1216, 77% of the research productivity, and followed by Science and Technology subjects. The United States of America 589; 37.1%, United Kingdom 318; 20%, and Canada 80; 5% got top three positions from the contribution of sixty[1]eight countries. Conclusion: Philosophy of education has the power to move society towards wisdom, to clarify the beliefs, strengthen values, relevant to intellectual thoughts of person and community, increase visualization of the spectrum of science and technological education.